When it's (mostly) the taking part that counts: the post-application consequences of employment tribunal claims - Stephen Drinkwater; Paul L. Latreille; K.G. Ben Knight (Institute for the Study of Labor (IZA), 2008)
This paper uses the 2003 Survey of Employment Tribunal Applications to examine the post-application employment consequences for individuals registering complaints to Employment Tribunals following dismissal or redundancy. In examining this issue, we consider a number of pieces of evidence: (i) the probability of finding another job; (ii) the time taken to get a new job and (iii) the pay/status of the new job. It is found that age plays a significant role in aspects (i) and (iii), whilst those who previously held managerial positions generally took longest to get a new job and found it most difficult to achieve a similar level of pay/status in their current jobs. Long-term health problems/disability is associated with significantly worse outcomes on all three measures. Respondents whose cases were dismissed by the tribunals without hearings fared worst in terms of obtaining a new job and the time it took to do so compared with other outcomes. There were, however, fewer differences by outcome in the relative pay/status of the claimant's current job.
urn:nbn:de:101:1-20080820149
Keywords: K4; 330; Employment tribunals; job separations; job search; Arbeitsrechtsprechung; Kündigung; Arbeitsuche; Dauer; Berufliche Integration; Erwerbsstatus; Großbritannien